Pembelajaran Garap Tari Untuk Anak Autis (Kajian Substansi Psikologi, Terapi Musik Tari di Sekolah Home Schooling Insan Mandiri) - Suari, Ni Made Pande; Trisnawati, Ida Ayu (STKIP AGAMA HINDU SINGARAJA, 2024)
Children on the autism spectrum (autism) often face challenges in social interaction, communication, and expressing emotions. For them, understanding and responding to sensory stimuli and social situations can be complicated. However, through an interdisciplinary approach that combines psychology, music therapy, and dance, dance learning has been proven to be an effective method for helping autistic children overcome these obstacles. This article will explain why learning to dance which involves psychology, music therapy and dance has a positive impact on the development of children with autism. Contributions that can be made after carrying out the learning process, children who have autistic disorders, they are able to appear in Home Scooling school graduation performances, with very good application, starting from the level of imagination which supports very well, can produce very good dances above. performance stage. So that you can contribute to the school well.